# logy=alogx

## Simple and best practice solution for logy=alogx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for logy=alogx equation:

Simplifying
logy = alogx
Solving
gloy = aglox
Solving for variable 'g'.
Move all terms containing g to the left, all other terms to the right.
Add '-1aglox' to each side of the equation.
-1aglox + gloy = aglox + -1aglox
Combine like terms: aglox + -1aglox = 0
-1aglox + gloy = 0
Factor out the Greatest Common Factor (GCF), 'glo'.
glo(-1ax + y) = 0
Subproblem 1Set the factor 'glo' equal to zero and attempt to solve:
Simplifying
glo = 0
Solving
glo = 0
Move all terms containing g to the left, all other terms to the right.
Simplifying
glo = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-1ax + y)' equal to zero and attempt to solve:
Simplifying
-1ax + y = 0
Solving
-1ax + y = 0
Move all terms containing g to the left, all other terms to the right.
Add 'ax' to each side of the equation.
-1ax + ax + y = 0 + ax
Combine like terms: -1ax + ax = 0
0 + y = 0 + ax
y = 0 + ax
Remove the zero:
y = ax
Add '-1y' to each side of the equation.
y + -1y = ax + -1y
Combine like terms: y + -1y = 0
0 = ax + -1y
Simplifying
0 = ax + -1y
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`